Evaluation of a Type 2 diabetes risk reduction online program for women with recent gestational diabetes: a randomised trial - Rachael Taylor; Megan E. Rollo; Jennifer N. Baldwin; Melinda Hutchesson; Elroy J. Aguiar; Katie Wynne; Ashley Young; Robin Callister; Clare E. Collins (BMC, 2022)
Abstract Background To evaluate the preliminary efficacy, feasibility and acceptability of the 3-month Body Balance Beyond (BBB) online program among Australian women with overweight/obesity and recent gestational diabetes mellitus. Methods Women were  randomised into either: 1) High Personalisation (HP) (access to 'BBB' website, video coaching sessions, text message support); 2) Medium Personalisation (MP) (website and text message support); or 3) Low Personalisation (LP) (website only). Generalised linear mixed models were used to evaluate preliminary efficacy, weight, diet quality, physical activity levels, self-efficacy and quality of life (QoL) at baseline and 3-months. Feasibility was assessed by recruitment and retention metrics and acceptability determined via online process evaluation survey at 3-months. Results Eighty three women were randomised, with 76 completing the study. Self-efficacy scores showed significant improvements in confidence to resist eating in a variety of situations from baseline to 3-months in HP compared to MP and LP groups (P=.03). The difference in mean QoL scores favoured the HP compared to MP and LP groups (P=.03). Half of the women (HP n=17[81%], MP n=12[75%], LP n=9[56%]) lost weight at 3-months. No significant group-by-time effect were reported for other outcomes. Two-thirds of women in the HP group were satisfied with the program overall and 86% would recommend it to others, compared with 25% and 44% in the MP group, and 14% and 36% in the LP group, respectively. Conclusions Video coaching sessions were associated with improvements in QoL scores and self-efficacy, however further refinement of the BBB website and text messages support could improve program acceptability. Trial registration Australian New Zealand Clinical Trials Registry (ANZCTR): ACTRN12619000162112 , registered 5 February 2019.